Distribution of Heterocarpus laevigatus Bate, 1888 and Plesionika escatilis (Stimpson, 1860) along the Atlantic coast of South America (Crustacea: Caridea: Pandalidae) - Viana, Girlene Fábia Segundo; Ramos-Porto, Marilena; Torres, Maria Fernanda Abrantes; Santos, Maria Do Carmo Ferrão (Zootaxa, 2007)
The family Pandalidae has a cosmopolitan distribution, occurring from the coastal region to more than 3000 meters of depth, and includes some species of economic importance. Three genera occur from Brazil: Heterocarpus A. Milne Edwards, 1881, Plesionika Bate, 1888 and Pandalus Leach, 1814. During the collections of the Programa de Avaliação dos Recursos Vivos da Zona Econômica Exclusiva of Brazil (REVIZEE, Northeast Score) a male of Heterocarpus laevigatus was collected in Pernambuco State, at a depth of 500m and fourteen females and four males of Plesionika escatilis were collected off the States of Pernambuco, Alagoas and Bahia, in depths varying from 93 to 260m. These records supplement the information on the distribution of these species, and represent the first records of H. laevigatus and P. escatilis from the Atlantic coast of South America.